Food science and the culinary arts - Gibson, Mark (Academic Press is an imprint of Elsevier, 2018)
"Food Science and the Culinary Arts is a unique reference that incorporates the principles of food and beverage science with practical applications in food preparation and product development. The first part of the book covers the various elements of the chemical processes that occur in the development of food products. It includes exploration of sensory elements, chemistry, and the transfer of energy and heat within the kitchen. The second part looks in detail at the makeup of specific foodstuffs from a scientific perspective, with chapters on meat, fish, vegetables, sugars, chocolate, coffee, and wine and spirits, among others. It provides a complete overview of the food science relevant to culinary students and professionals training to work in the food industry. Provides foundational food science information to culinary students and specialists. Integrates principles of food science into practical applications. Spans food chemistry to ingredients, whole foods, and baked and mixed foodsIncludes a comprehensive glossary of terms in food science"--